Reciprocity or Community? Different Cultural Pathways to Cooperation and Welfare - Gunnthorsdottir, Anna; Thorsteinsson, Palmar; Olafsson, Sigurdur P. (Cross-Cultural Research, 2024)
We compare efficiency-enhancing cooperation and its underlying motives in Iceland and the US. The two countries are distinct along all measures of national culture known to us. They are however both developed democracies with similar GDP/capita (PPP adjusted). These similarities make it possible to hold constant aspects of culture related to wealth and institutions. In an experimental Voluntary Contribution Mechanism (VCM), we prime the participants with different social foci, emphasizing either their directly cooperating team or their wider social unit. With a team focus, cooperation levels do not differ between the two cultures, but this superficial similarity masks deep-seated differences: When the focus is on the wider social unit cooperation increases in Iceland and declines in the US. Both when the contribution levels are the same and when they differ, members of the two cultures differ in their motives to cooperate: Icelanders tend to cooperate unconditionally, and US subjects conditionally with a strong emphasis on reciprocity. Our findings indicate that different cultures can achieve similar economic and societal performance through different cultural norms and suggest that cooperation should be encouraged through culturally tailored persuasion tactics.